2019
DOI: 10.3389/fvets.2019.00445
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Fencing Is Comparable to Electric Tape Fencing for Cattle Behavior and Welfare

Abstract: Virtual fencing technology restricts animal movement via communicated signals without physical boundaries. Specifically, the eShepherd TM automated virtual fencing system operates via GPS technology and provides stimuli via a neckband device. An audio warning tone is emitted at the virtual boundary which is followed by an electrical pulse if the animal continues moving forward. Animal welfare is a priority consideration for the commercial implementation of virtual fencing systems. The current study assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 26 publications
5
89
1
5
Order By: Relevance
“…This brings in the potential for differences in environmental conditions that may have affected behaviour of the sheep in this study. With the development of automated collars, longer term larger scale replicated studies will be possible, as have been demonstrated in cattle (Campbell et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This brings in the potential for differences in environmental conditions that may have affected behaviour of the sheep in this study. With the development of automated collars, longer term larger scale replicated studies will be possible, as have been demonstrated in cattle (Campbell et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural time budgets have been used previously in cattle (Campbell et al, 2017;Campbell et al, 2019) and sheep (Marini et al, 2018a) exposed to virtual fencing, as indicators of impact to welfare through behavioural change. Another method of measuring impact on welfare includes measures of body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This warrants further study. Previous research has reported no significant behaviour or welfare impacts in beef cattle [ 11 ] or in sheep [ 10 ]. However, long term behaviour and welfare monitoring should be conducted to identify any animals that are unable to learn, and would, therefore, not be suited to the VF system [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive punishment training methods can have welfare implications, particularly if delivery is inconsistent, which affects an animal’s ability to learn [ 8 , 9 ]. Previous studies have demonstrated that the stress response to handling was greater than the response to VF stimuli in sheep [ 10 ], and the response of cattle to electrical stimuli was comparable to an electric fence [ 11 ]. The consistent delivery of stimuli (AT before EP) based on the animal’s behaviour, location and direction ensure predictability and controllability [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation